Security management in wireless sensor networks with a public key based scheme - Pathan, Al-Sakib Khan; Ryu, Jae Hyun; Haque, Md. Mokammel; Hong, Choong Seon (Springer-Verlag, 2007)
This paper proposes an efficient approach for managing the security in WSN. Our approach uses the notion of public key cryptography in which two different keys are used for encryption and decryption of data. Our analysis and performance evaluations show that, our approach is viable with the specifications of today's Berkley/Crossbow MICA2dot motes.